The dividends received deduction in the corporate income tax and cost of capital - Dominik Rumpf (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2011)
This paper provides a model-based analysis of special tax rules for corporations that invest in stocks of other corporations. To avoid double taxation the returns from such stock investments (dividends and capital gains) are usually tax-exempted or taxed at a reduced tax rate. This allows for considerable tax avoidance strategies, which are typically ignored when valuing firms or assessing investment projects. A comparison of several major industrial countries yields the result that especially German corporations can achieve a benefit easily. Integrating assumptions about the character of restricted financial structures, it is possible to link this tax benefit to a new investment in normal-taxed assets. This allows calculating the reduction in an investment's cost of capital. All in all, the results indicate a substantial impact of the analyzed strategy on investment decisions and on valuations of firms as the benefit's magnitude is comparable to that of the common tax shield. Although a single corporation does not necessarily extend its leverage ratio by adopting this strategy, the corporate sector as a whole tends to be more levered and thus more vulnerable to economic crises. The current tax rules, therefore, foster systemic risk of the corporate sector. This could be avoided by implementing a fundamental tax reform which guarantees undistorted debt-equity decisions.
Keywords: G11; G32; H25; 330; Corporate Finance; Debt-equity Decision; Corporate Income Tax; Dividend Received Deduction